2016
DOI: 10.14569/ijacsa.2016.070565
|View full text |Cite
|
Sign up to set email alerts
|

An Enhencment Medical Image Compression Algorithm Based on Neural Network

Abstract: Abstract-The main objective of medical image compression is to attain the best possible fidelity for an available communication and storage [6], in order to preserve the information contained in the image and does not have an error when they are processing it. In this work, we propose a medical image compression algorithm based on Artificial Neural Network (ANN). It is a simple algorithm which preserves all the image data. Experimental results performed at 8 bits/pixels and 12bits/pixels medical images show th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 15 publications
0
7
0
1
Order By: Relevance
“…The performance of the proposed approach was validated by comparing it with other existing approaches and the observations are tabulated. From the results, it can be observed that the proposed approach achieved a dice score of 0.71 for whole tumor (WT), 0.80 for core tumor (CT), and 0.82 for active tumor (AT) compared to other approaches and the parameters for segmented tissues and its performance anal-sis are evaluated and the obtained results show the efficacy of the proposed approach [46][47][48][49][50][51][52].…”
Section: Conclusion and Future Scopementioning
confidence: 91%
See 1 more Smart Citation
“…The performance of the proposed approach was validated by comparing it with other existing approaches and the observations are tabulated. From the results, it can be observed that the proposed approach achieved a dice score of 0.71 for whole tumor (WT), 0.80 for core tumor (CT), and 0.82 for active tumor (AT) compared to other approaches and the parameters for segmented tissues and its performance anal-sis are evaluated and the obtained results show the efficacy of the proposed approach [46][47][48][49][50][51][52].…”
Section: Conclusion and Future Scopementioning
confidence: 91%
“…Considering an example of knowledge obtained during the process of recognizing humans. This knowledge can be applied to learn and recognize different humans at various age levels [46]. This process is the learning process of the machine, using external sources of additional training information from one or more related tasks considering the basic training data.…”
Section: Training Neural Network Using Transfer Learningmentioning
confidence: 99%
“…The most common neural network used for image compression is feed-forward artificial neural networks. They contain a minimum of one hidden layer, with fewer neurons than the input and output layers, depending on the compression ratio required, and such structure is known as bottleneck architecture [14]. This bottleneck architecture allows the neural network to map the original information onto a lower-dimensional manifold from which the original information can be predicted i.e.…”
Section: Methodsmentioning
confidence: 99%
“…Entropy is a magnitude characterizing the quantity of data contained in an image. In fact, if the dispensing of grey values is very uniform, the information entropy is greater [39,40]. e entropy E(s) is defined by the following equation:…”
Section: E Entropymentioning
confidence: 99%